99mTc-Labeled FAPI SPECT Imaging in Idiopathic Pulmonary Fibrosis: Preliminary Results - Yu Liu; Qian Zhang; Yuwei Zhang; Jingnan Wang; Yitian Wu; Guangjie Yang; Jiyun Shi; Fan Wang; Zuojun Xu; Hongli Jing (MDPI AG, 2023)
Aim: Idiopathic pulmonary fibrosis (IPF) is associated with a poor prognosis, presenting the most aggressive form of interstitial lung diseases (ILDs). Activated fibroblasts are crucial for pathological processes. Fibroblast activation protein (FAP) inhibitor (FAPI) tracers would be promising imaging agents for these diseases. The purpose of this study was to evaluate a 99mTc-labeled FAPI tracer, 99mTc-HFAPI imaging in IPF patients. Methods: Eleven IPF patients (nine males and two females; age range 55-75 year) were included in this pilot study. 99mTc-HFAPI serial whole-body scintigraphy at 5 min, 20 min, 40 min, 1 h, 2 h, 3 h, 4 h, and 6 h was acquired for dynamic biodistribution and dosimetry estimation in seven representative patients. SPECT/CT tomography fusion imaging of the chest region was performed in all patients at 4 h post-injection, which was considered as the optimal acquisition time. Dosimetry was calculated using OLINDA/EXM software (version 2.0; HERMES Medical Solutions). The quantified or semi-quantified standardized uptake values (SUVs) and lesion-to-background ratios (LBRs) of affected lung parenchyma were also calculated. The high-resolution CT (HRCT) stage was determined with visual evaluation, and the total HRCT score of each patient was measured using a weighting factor formula. Pulmonary function tests (PFTs) were recorded as well. Then, the relationships between the 99mTc-HFAPI results, disease extent on HRCT, and PFT results were investigated. Results: Normal physiological uptake of 99mTc-HFAPI was observed mainly in the liver, intestinal tract, pancreas, gallbladder, and to a lesser extent in the spleen, kidneys, and thyroid, with no apparent retention in the blood circulation at the late time point. The mean injected activity of 99mTc-HFAPI was 813.4 MBq (range 695.6-888.0 MBq). No subjective side effects were noticed. The average whole-body effective dose was 0.0041 mSv/MBq per patient. IPF patients exhibited elevated pulmonary 99mTc-HFAPI uptake in abnormal lung regions, which was correlated with fibrotic regions on HRCT. Among different HRCT stage groups, both SUVmax and LBR showed significant differences (p < 0.001). The higher HRCT stage demonstrated significantly higher SUVmax and LBR. A linear correlation between 99mTc-HFAPI uptake and total HRCT score was observed for SUVmax (r = 0.7839, F = 54.41, p = 0.0094) and LBR (r = 0.7402, F = 56.33, p = 0.0092). 99mTc-HFAPI uptake also had moderate correlations with PFT results. Conclusions: Our preliminary data show that the 99mTc-HFAPI SPECT imaging is a promising new imaging modality in IPF patients. Investigations of its clinical value in monitoring disease progression and treatment response are needed in the future.